Transient Arterial Hypertension Induced by Gonadotropin-Releasing Hormone Agonist Treatment for Central Precocious Puberty - Sifaki, Loukia; Cachat, Francois; Theintz, Gerald; Chehade, Hassib (Frontiers in Pediatrics, 2019)
Background: Gonadotropin-releasing hormone agonists (GnRHa) are a safe and effective treatment for precocious puberty. Triptorelin is one of the long lasting GnRHa, which reversibly suppresses the pituitary-gonadal axis. Triptorelin-induced hypertension (HTN) has rarely been reported in the literature. Clinical Case/Methods: We report a 10-year-old girl with central precocious puberty who, during treatment with triptorelin, developed an asymptomatic stage II HTN. Initial workup showed no renal, thyroid or electrolytes abnormalities. The renal ultrasound showed no parenchymal disease and no increased renal resistance index suggestive of a renal artery stenosis. Echocardiography and ocular fundoscopy were normal. HTN (stage II) was confirmed with ambulatory blood pressure monitoring (ABPM). After extensive literature review, we found 3 other cases of HTN secondary to GnRHa, improving with endocrine treatment cessation. Therefore, antihypertensive treatment was not started immediately in our patient. Indeed, after completion of her treatment with triptorelin, we observed a complete normalization of her blood pressure (confirmed with ABPM) without any medication. Conclusion: Concomitantly to GnRHa treatment, our patient developed HTN, which completely subsided after stopping triptorelin. The complete normalization of her blood pressure, together with a negative workup for HTN strongly speaks for a causal effect of her endocrine treatment. In this setting, estrogen depletion might play a role, although this remains debated.